RANCANGAN HOUSE OF ERGONOMIC INTERIOR TOILET GERBONG KERETA PENUMPANG KELAS EKONOMI MENGGUNAKAN METODE ERGONOMIC FUNCTION DEPLOYMENT - Gita Permata Liansari; Asterina Adi Febrianti; Putra Adi Tama Gt. (Universitas Mercu Buana, 2018)
Today, trains being the most popular transportation mode. A lot of people choosing this transportation to hold for far destinations. Customer satisfaction is the important thing for all of industries, such as PT KAI. The completeness and renewal of facility in trains being one of factor for achieving that. Toilet is one of the most important support facilities on passengers train cars and indeed many complaints from passengers about it. Toilets located in passenger train cars have drawbacks, especially on the use of available space, material used, and cleanliness of the toilet. In this research doing design of HOE for toilet interior using Ergonomic Function Deployment (EFD) method.